Low-dose vs. standard-dose alteplase for acute ischemic stroke: a real-world single-center retrospective study - Mao, Xin-Lei; He, Si-Si; Zhang, Ya-Xi; Lin, Cai-Dan; Chen, Xin-Xin; Zhang, Shi-Zheng; Ge, Li-Na; Zhuang, Qing-Qing (Frontiers in Neurology, 2025)
ObjectivesTo investigate the real-world usage patterns and clinical outcomes of low-dose (0.6 mg/kg) versus standard-dose (0.9 mg/kg) intravenous alteplase in patients with acute ischemic stroke (AIS).MethodsThis single-center retrospective study included 707 patients with AIS who received intravenous thrombolysis at Wenzhou Central Hospital from December 2016 to April 2023. Baseline characteristics, treatment selection, and clinical outcomes were analyzed. The primary outcomes were 90-day functional outcomes (mRS 0–1 and mRS 0–2) and the incidence of symptomatic intracranial hemorrhage (sICH).ResultsLow-dose alteplase was more commonly used in older patients (p < 0.001) and in those on pre-stroke antithrombotic medications (p < 0.01). Junior physicians were more inclined to use low-dose alteplase compared to senior physicians (p < 0.001). The coefficient of variation in rt-PA dosage selection among different physicians was as high as 61%. There were no significant differences in 90-day functional outcomes (mRS 0–1: OR 0.87, 95% CI 0.62–1.23, p = 0.43; mRS 0–2: OR 1.09, 95% CI 0.78–1.52, p = 0.63) or the incidence of sICH (by NINDS criteria: OR 1.68, 95% CI 0.78–3.62, p = 0.19) between the low-dose and standard-dose groups.ConclusionThe study highlights the complexity of treatment decision-making for intravenous alteplase in AIS, with significant influences from both patient and physician factors. Low-dose alteplase demonstrated similar clinical outcomes to standard-dose alteplase in this real-world setting. Future research should focus on optimizing treatment decisions and improving guideline adherence to enhance patient outcomes.